Compulsive behaviour - Gabriel, Andriani; Tarlow, Manio (Open Schools Journal for Open Science, 2024)
Compulsive behaviour is characterized by strong physical or psychological urges to engage in activities or use substances, often without regard for the consequences. These behaviours can lead to significant impairment in personal, social, and occupational functioning. This paper explores the nature of compulsive behaviours, their prevention, various types, symptoms, diagnosis, and treatment. Emphasis is placed on the importance of mental and physical health in recovery from compulsive behaviours.